Studi Kualitatif Syirkah Implikasinya pada Bank Syariah dan Lembaga Keuangan Syariah - Karmila Sari; Indra Saputra; Angga Rizki Prawira; Aidil Alfin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the Qualitative Study of Shirkah, Its Implications on Sharia Banks and Sharia Financial Institutions. This study uses a qualitative approach with a type of literature study (library research). This method aims for a Qualitative Study of Shirkah, Its Implications on Sharia Banks and Islamic Financial Institutions, focusing on the application of application in daily life. The data in this study were collected through the search of relevant documents and secondary sources, such as Articles from national and international journals indexed by SINTA and Scopus, related to shirkah and its Application to Sharia Bank Transactions. The result of the research is that the musyarakah contract is recorded and witnessed. Second, the contracting party: it is required that the partner must be competent in granting or being given the power of representation. The three objects of the contract (funds and work): the capital provided must be in cash, gold, silver, or of the same value. The ulama agree on this.